Engineering Quality Improvement Of Kuantan Clay Subgrade Using Recycling And Reused Materials as Stabilizer - Achmad Fauzi, Abdul Wahab; Fauzi, Usama Juniansyah; Wan Mohd Nazmi, Wan Abdul Rahman (Elsevier Ltd, 2013)
This paper proposes an engineering quality improvement of Kuantan clay subgrade using fly ash, bottom ash and oil palm empty fruit bunches (OPEFB) ash as stabilizer in highway construction. The research conducts soil engineering properties and strength test for various contents of fly ash, bottom ash and OPEFB ash to different types of clay soil from various sites in Kuantan. Standard compaction and California Bearing Ratio (CBR) were applied in soil samples to estimate the optimum mixture design. The samples were set up by mixing soil samples with various content of stabilizer at optimum water content. The accomplishment of subgrade stabilization depends on the engineering properties of clay and characteristic of stabilizer. The laboratory result shows that the strength gain in stabilization mainly depends on stabilizer content and molding water content. The variation content of fly ash, bottom ash, OPEFB ash were 4%, 8% and 12% by dry total weight (Fauzi and Wan 2010; Fauzi et al. 2010; Fauzi et al. 2011; Hilmi et al. 2006).